2011
DOI: 10.1016/j.neuroimage.2010.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Factors underlying prefrontal and insula structural alterations in smokers

Abstract: Based upon previous reports of alterations in white matter integrity and gray matter density in smokers, we examined these markers in a large, well-matched sample of smokers and non-smokers. We further investigated the effect of heavy cigarette exposure by using pack-years and the effects of two relatively stable, highly heritable traits in smokers (Fagerström Test of Nicotine Dependence (FTND), a measure of severity of nicotine dependence so and Toronto Alexithymia Scale (TAS-20), measuring a stable personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
159
3
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(179 citation statements)
references
References 64 publications
15
159
3
2
Order By: Relevance
“…Effects of continued exposure may explain reports of lower gray-matter density in insula in adult smokers than nonsmokers (Gallinat et al, 2006;Zhang et al, 2011a). Although one study reports greater insula graymatter density in adult smokers than nonsmokers, left insula density was correlated with symptoms of alexithymia, but not with cigarette exposure or dependence (Zhang et al, 2011a), suggesting that other factors comorbid with smoking may contribute to the discrepant results. Differences in the methods used to index gray-matter integrity could also contribute to the heterogeneity in the literature.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Effects of continued exposure may explain reports of lower gray-matter density in insula in adult smokers than nonsmokers (Gallinat et al, 2006;Zhang et al, 2011a). Although one study reports greater insula graymatter density in adult smokers than nonsmokers, left insula density was correlated with symptoms of alexithymia, but not with cigarette exposure or dependence (Zhang et al, 2011a), suggesting that other factors comorbid with smoking may contribute to the discrepant results. Differences in the methods used to index gray-matter integrity could also contribute to the heterogeneity in the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Participants in this study began smoking in adolescence (mean age of initiation: 15.1 years old), and studies in animals indicate that exposure to nicotine during adolescence reduces the number of cells in the cerebral cortex by 5-10% as indexed by DNA content; however, DNA content was measured in fairly gross anatomical regions precluding determination of anatomical specificity and possibly masking the true magnitude of the effect (Slotkin, 2002). Effects of continued exposure may explain reports of lower gray-matter density in insula in adult smokers than nonsmokers (Gallinat et al, 2006;Zhang et al, 2011a). Although one study reports greater insula graymatter density in adult smokers than nonsmokers, left insula density was correlated with symptoms of alexithymia, but not with cigarette exposure or dependence (Zhang et al, 2011a), suggesting that other factors comorbid with smoking may contribute to the discrepant results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies have shown mixed results as to whether drug addiction was associated with increased or decreased gray matter volume in the insula. One study found that METH-dependent subjects had smaller left insula compared to CON (Morales et al, 2012), but another study found higher gray matter density in cigarette smokers in the left anterior insula compared to nonsmokers (Zhang et al, 2011). The inconsistencies could be due to differences in methodologies.…”
Section: Right Insula Volume In Meth Usersmentioning
confidence: 99%
“…Besides physical health problems, chronic smoking causes functional and structural abnormalities in the brain [2][3][4][5]. However, most chronic smokers, including those who are willing to quit, find it difficult to become free of tobacco usage even with the help of intervention methods such as pharmacotherapy [6].…”
Section: Introductionmentioning
confidence: 99%